A deformation rig for synchrotron microtomography studies of geomaterials under conditions down to 10 km depth in the Earth. (16th June 2016) - Renard, François; Cordonnier, Benoit; Dysthe, Dag K.; Boller, Elodie; Tafforeau, Paul; Rack, Alexander
Abstract : A new rig developed to study time‐lapse deformation of solid samples using in situ microtomography (up to 250°C and 1000 bar) is described. Abstract : A hard X‐ray transparent triaxial deformation apparatus, called HADES, has been developed by Sanchez Technologies and installed on the microtomography beamline ID19 at the European Radiation Synchrotron Facility (ESRF). This rig can be used for time‐lapse microtomography studies of the deformation of porous solids (rocks, ceramics, metallic foams) at conditions of confining pressure to 100 MPa, axial stress to 200 MPa, temperature to 250°C, and controlled aqueous fluid flow. It is transparent to high‐energy X‐rays above 60 keV and can be used for in situ studies of coupled processes that involve deformation and chemical reactions. The rig can be installed at synchrotron radiation sources able to deliver a high‐flux polychromatic beam in the hard X‐ray range to acquire tomographic data sets with a voxel size in the range 0.7–6.5 µm in less than two minutes.